A concepção do indicador analfabetismo nas mudanças censitárias no Brasil - Ada Augusta Celestino Bezerra; Dinamara Garcia Feldens; Márcia Alves de Carvalho Machado (Araucaria)
This article aims to characterize the design changes as illiteracy indicator along the census surveys in Brazil, published from 1920 to the present day and its implications. In this sense, it is an analysis from the survey of concepts and literacy requirement of the features in the census, considering the conceptual and methodological changes that have occurred throughout history. In the study design we used the procedures of bibliographic research, field and documental. During the analysis confirmed the hypothesis that the concept of literacy in censuses of Brazil, although it has changed over the years 1950, 1980 and 2000 did not incorporate the expansion of its significance with regard to its epistemological evolution and methodological. Thereby, this information mistakenly subsidize the formulation of public policies in this area, preventing them to be the most suitable for overcoming illiteracy.